JURNAL ILMU KEHUTANAN : Modeling The Fate of Sumatran Elephants in Bukit Tigapuluh, Indonesia : Research Needs & Implications for Population Management - Alexander Markus Mosbrucker , Muhammad Ali Imron (Fakultas Kehutanan UGM, 2016)
The critically endangered Sumatran elephant persists in mainly small and isolated populations that may require intensive management to be viable in the long term.